Barthes in a Post-Colonial Guatemala: Dismantling the National Hero - Monterroso, Jamie (Romance eReview, 2017)
In Guatemala the myth of the national hero is celebrated and commemorated every year despite its oppressive character. Although the myth is oppressive, it functions as a way to maintain the values of the ruling class; in this case, the ladinos, or the descendants of European colonizers. The myth of the national hero portrays a Mayan prince who lost the battle to the “knowledgeable” Pedro de Alvarado because of this “inherent” and “natural” ignorance. In order to understand how the oppressive character of this myth is overlooked by a society, it is important to understand what Roland Barthes says in his essay “Myth Today” in the collection of essays in Mythologies. There, Barthes explains that myth, as a particular form of speech, obscures and naturalizes the values of the ruling class by portraying them in a way that seems innocent and natural. This of course, Barthes argues, is a specific function of myth that occurs when two chains of signification converge into a single sign that transforms meaning into form; history into nature. For this reason, it is imperative that a society, such as the Guatemalan society, which can be described as trying to overcome its colonial past, dismantles the “innocence” of the national myth that not only shapes the national identity but also oppresses its people. In this way, Barthes’ work on myth is imperative, not only in the broader sense to cultural and post-colonial studies, but also in particular to the Guatemalan nationalistic anti-hero. However, the question remains on how post-colonial thinkers can utilize Barthes’ theory given his European background.